Blood clot-inspired viscoelastic fibrin gel: New aqueous binder for silicon anodes in lithium ion batteries - Kim, Woong-Ju; Kang, Jin Gu; Kim, Dong-Wan (Elsevier BV, 2022)
Binders are a key component of Si anodes for lithium-ion batteries. Many studies have been devoted to exploring new binders capable of suppressing electrical isolation under large volume changes of Si. The principal requirements for a good binder are a high level of surface polarity and mechanical stability. One class of binders receiving attention is those composed of polysaccharide building blocks. Inspired by blood clots, we propose a new binder based on fibrin, whose building blocks are amino acids. Its abundant polar functional groups and time-dependent viscoelastic behavior make fibrin attractive as a binder in Si anodes. Our fibrin-based Si electrode shows better cycling stability and rate performance than an alginate-based electrode. Further optimization by mixing fibrin with alginate and ionic cross-linking results in an advanced binder that demonstrates remarkable cycling stability between 0.01 and 1.0 V vs. Li/Li+ (740 mA h g(- 1) at 0.5 C after 500 cycles). This improved electrochemical property derives from the mechanical integrity of the electrode, which can be achieved by a balance between the stiffness and stress relaxation of the binder. This work highlights the potential of fibrin as a novel binder for Si anodes and offers guidance for the design of optimized binders.